PENGARUH PELATIHAN DAN LINGKUNGAN KERA TERHADAP KEPUASAN KERJA PERAWAT PADA RS.ISLAM IBNU SINA PEKANBARU - Putri, Amelia; ', Suryalena (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research was conducted to determine and analyze the influence of training and work environment on the job satisfaction of inpatient nurses in hospitals. Islam Ibn Sina Pekanbaru. The independent (free) variables in this study are training (X1) and work environment (X2), and the dependent variable in this study is nurse job satisfaction (Y). The problem in this research is the high turnover rate of nurses at Ibnu Sina Islamic Hospital which is shown based on turnover data for the last 5 years. The research method in this research is a quantitative method. The population in this study was 76 and the sample in this study was 52 nurses using a sampling technique, namely purposive sampling. The data source in this research is primary data obtained by researchers from the results of distributing questionnaires to 52 nurses at the hospital. Islam Ibnu Sina Pekanbaru which was then classified statistically using the SPSS 24 program. The results obtained in this study show that it is partially known that training has an influence on nurses' job satisfaction, it is partially known that the work environment has an influence on nurses' job satisfaction, simultaneously training and The work environment has an influence on nurses' job satisfaction Keywords: Service Quality, Product Quality, Pricing, Consumer Satisfaction